Real world impact of 13vPCV in preventing invasive pneumococcal pneumonia in Australian children: A national study. Issue 1 (4th January 2023) - Homaira, Nusrat; Strachan, Roxanne; Quinn, Helen; Beggs, Sean; Bhuiyan, Mejbah; Bowen, Asha; Fawcett, Laura K; Gilbert, Gwendolyn L; Lambert, Stephen B; Macartney, Kristine; Marshall, Helen S; Martin MD, Andrew C; et al.
Highlights: Comprehensive national analysis of the impact of 13 valent pneumococcal conjugate vaccine (13vPCV) on invasive pneumococcal pneumonia (IPP) hospitalisations in Australian children based on more than three years of prospective molecular surveillance data after introduction of 13vPCV into the National Immunisation Program in July 2011 (3 + 0 dose). Our results suggest 13vPCV failed to provide protection against IPP in Australian children specifically IPP due to vaccine specific serotypes (STs) 3 and 19A. Our results also suggest only a small proportion of all IPP cases has been caused by non-vaccine STs in 13vPCV era. The study findings highlight the need for new generation of pneumococcal vaccines. In addition, as Australia moved to 2 + 1 dose schedule for 13vPCV in 2018, enhanced molecular surveillance to monitor the impact of changed schedule of 13vPCV on IPP will help guide policy recommendations for future vaccine schedule and formulation. Abstract: Background: We aimed to assess the direct protective effect of 13 valent pneumococcal conjugate vaccine (13vPCV) against invasive pneumococcal pneumonia (IPP; including pneumonia and empyema) in children using a nation-wide case-control study across 11 paediatric tertiary hospitals in Australia. Methods: Children < 18 years old admitted with pneumonia were eligible for enrolment. IPP was defined as Streptococcus pneumoniae (SP) cultured or detected by polymerase chain reaction (PCR) from blood or pleural fluid. Causative SP serotype (ST) was determined from blood or pleural fluid SP isolates by molecular methods in PCR positive specimens or else inferred from nasopharyngeal isolates. For each IPP case, 20 population controls matched by age and socio-economic status were sampled from the Australian Immunisation Register. Conditional logistic regression was used to estimate the adjusted odds ratio (aOR) of being fully vaccinated with 13vPCV (≥3 doses versus < 3 doses) among IPP cases compared to controls, adjusted for sex and Indigenous status. Results: From February 2015 to September 2018, we enrolled 1, 168 children with pneumonia; 779 were 13vPCV-eligible and were individually matched to 15, 580 controls. SP was confirmed in 195 IPP cases, 181 of whom had empyema. ST3 and ST19A were identified in 52% (102/195) and 11% (21/195) of IPP cases respectively. The aOR of being fully vaccinated with 13vPCV was 0.8 (95% CI 0.6–1.0) among IPP cases compared to matched controls. Conclusion: We failed to identify a strong direct protective effect of 13vPCV against IPP among Australian children, where disease was largely driven by ST3.